2017
DOI: 10.1007/s10339-016-0789-y
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and emotional demands of black humour processing: the role of intelligence, aggressiveness and mood

Abstract: Humour processing is a complex information-processing task that is dependent on cognitive and emotional aspects which presumably influence frame-shifting and conceptual blending, mental operations that underlie humour processing. The aim of the current study was to find distinctive groups of subjects with respect to black humour processing, intellectual capacities, mood disturbance and aggressiveness. A total of 156 adults rated black humour cartoons and conducted measurements of verbal and nonverbal intellige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 28 publications
0
15
1
2
Order By: Relevance
“…For the degree of anger, aggression improved the degree of anger of the materials in the present study, which was consistent with Anderson’s (2002) conclusion that aggressive attack could trigger anger. It suggested that higher aggressiveness apparently leads to decreased levels of pleasure (Willinger et al, 2017), which is inconsistent with our finding, probably because their materials were not point-to-self. It reminds us that the direction of humor can influence humor processing and therefore the future study of humor would pay attention on the direction of humor.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…For the degree of anger, aggression improved the degree of anger of the materials in the present study, which was consistent with Anderson’s (2002) conclusion that aggressive attack could trigger anger. It suggested that higher aggressiveness apparently leads to decreased levels of pleasure (Willinger et al, 2017), which is inconsistent with our finding, probably because their materials were not point-to-self. It reminds us that the direction of humor can influence humor processing and therefore the future study of humor would pay attention on the direction of humor.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous behavioral experiments have shown that aggression increased the degree of funniness of humor materials (Epstein and Smith, 1956) and led to decreased levels of pleasure (Willinger et al, 2017). Further exploration showed that the materials with highly aroused aggression made participants feel more pleasure (Strickland, 1959; Dworkin and Efran, 1967).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, gender differences and changes with aging were shown to be amplified by the darker themes, with women and older adults judging this type of humor generally as less funny and more aversive (Aillaud and Piolat, 2012;Carretero-Dios and Ruch, 2010;Herzog et al, 2006;Herzog and Karafa, 1998;Johnson, 1992). In addition, one study also showed the role of education in perceived funniness: specifically, dark humor cartoons tended to be rated as funnier by participants with higher levels of educational attainment (Willinger et al, 2017). Concerning the role of personality traits, there is a vast number of studies on humor production and humor styles (e.g., Dozois et al, 2013;Papousek et al, 2017;Ruch et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that high aggressiveness in students is caused by low emotional and spiritual intelligence (Ahmed et al, 2016). Results of relevant studies show that there is a relationship between students' aggressiveness levels and emotional intelligence (Willinger et al, 2017;Mitrofan, 2018;García, Salguero, & Fernández 2017;Garaigordobil & Peña, 2015). Emotional intelligence (EQ) is viewed as one's ability to recognize one's and people's emotions and to know how to behave with others.…”
Section: Introductionmentioning
confidence: 99%